(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
A study has been carried out to analyse the temporal and seasonal patterns in the trends of diurnal air temperature range (DTR) and its components in Shaheed Benazir Abad for the time period 1996–2014.The magnitude, the slope and the significance of trends were investigated by using the linear regression method, the trend magnitude, the Mann-Kendall test and the Sen’s estimator of slope. The Mann-Kendall test and Sen’s estimator of slope were calculated by using Addinsoft’s XLSTAT 2015 software. The hypothesis of Mann-Kendall test was investigated at 95% confidence level for all variables. The result shows that minimum temperature of Shaheed Benazir Abad has increased at the rate of 0.063°C per year during study period while the maximum temperature for all months exhibits no change. This increase of minimum temperature contributed to the decreasing trend of diurnal temperature range. The DTR decreased at the rate of 0.057°C /year in Shaheed Benazir Abad. The investigation of seasonal DTR trends revealed that Summer and Spring seasons also witnessed a decreasing trends at the rate of 0.26 °C/year and 0.047°C/year respectively. Winter and aseasons, on the other hand, have experienced the increasing trends of DTR at the rate of 0.136 °C/year and 0.115 °C/year respectively. It is found by MK test that Tmax (winter), Tmax (Spring) and Tmin (Spring) exhibited the significant positive trends at the rate of 0.21°C/year, 0.368 °C/year and 0.421°C/year respectively. The increasing trends of Tmax of winter and spring indicate that winter and spring are warmer now.